2018
DOI: 10.1038/s41388-018-0183-6
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis-associated miR-23a from nasopharyngeal carcinoma-derived exosomes mediates angiogenesis by repressing a novel target gene TSGA10

Abstract: Benefiting from more precise imaging and radiotherapy, patients with locoregionally nasopharyngeal carcinoma (NPC) have a significantly higher survival rate. Nonetheless, distant metastasis is still the predominant mode of failure. Advances in cancer research have highlighted that pathological angiogenesis is necessary for tumor metastasis by offering oxygen, nutrients, or cell metastatic conduits. MicroRNAs (miRNAs), a class of small noncoding RNAs, are increasingly implicated in modulation of angiogenesis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
158
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 50 publications
1
158
0
Order By: Relevance
“…The main therapeutic strategies for NPC patients are chemoradiotherapy and radiotherapy . Even though great progress has been made in diagnosis and prognosis of NPC, the morbidity and mortality are high owing to local recurrence and systemic metastasis . Therefore, a better understanding of the molecular mechanisms of NPC may improve the diagnosis and prognosis of NPC patients.…”
Section: Introductionmentioning
confidence: 99%
“…The main therapeutic strategies for NPC patients are chemoradiotherapy and radiotherapy . Even though great progress has been made in diagnosis and prognosis of NPC, the morbidity and mortality are high owing to local recurrence and systemic metastasis . Therefore, a better understanding of the molecular mechanisms of NPC may improve the diagnosis and prognosis of NPC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that miR-23a can be carried by tumor cell-secreted exosomes such as nasopharyngeal carcinoma or lung cancer cells and then exert their regulatory functions on angiogenesis (22)(23)(24), which suggested that miR-23a carried by GC cell-derived exosomes might be involved in angiogenesis. To validate this hypothesis, exosomes were extracted from GES-1, NCI-N87, HGC-27, AGS, and MKN45 using the ExoQuick method and then identified.…”
Section: Mir-23a Is Enriched In Gc Cells-derived Exosomesmentioning
confidence: 99%
“…Angiogenesis is not a simple one‐to‐one correspondence regulated by exosomal miRNAs. Bao et al . detected and identified that highly enriched miR‐23a regulated angiogenesis by targeting gene TSGA10 in nasopharyngeal carcinoma (NPC; Table ).…”
Section: Exosome and Tumor Developmentmentioning
confidence: 99%
“…Angiogenesis is not a simple one-to-one correspondence regulated by exosomal miRNAs. Bao et al 49 detected and identified that highly enriched miR-23a regulated angiogenesis by targeting gene TSGA10 in nasopharyngeal carcinoma (NPC; Table 1). Under the hypoxic circumstance, Hsu et al 50 found that lung cancer-derived suppressing miR-23a in exosomes could upregulate prolyl hydroxylase 1 and 2 (PHD1 and 2), accumulated hypoxia-inducible factor-1 alpha (HIF-1 alpha) in endothelial cells so as to induce angiogenesis and promote vascular permeability ( Table 1).…”
Section: Cancer Metastasismentioning
confidence: 99%